2014
DOI: 10.1016/j.metabol.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Serum ionized magnesium in diabetic older persons

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. IntroductionThere is compelling evidence suggesting that magnesium depletion may play a role in the pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 43 publications
4
31
0
3
Order By: Relevance
“…These higher incidences could be explained by the fact that in that paper hypomagnesemia was defined as serum magnesium level below 1.8 mg/dl, in contrast to the present study in which 1.7 mg/dl was used as a cut-off to define hypomagnesemia. And indeed, if we re-analyze our data with a cut-off serum magnesium value of 1.8mg/dl, 15,1% of the entire population is diagnosed with hypomagnesemia: 11.5% of the overweight and obese patients and 32.6% of the patients with DM2, which is more in line with the Guerrero-Romero study and to studies performed in patients with DM2 (14% to 48%) [18][19][20]. Also, racial differences in serum magnesium levels have been reported.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These higher incidences could be explained by the fact that in that paper hypomagnesemia was defined as serum magnesium level below 1.8 mg/dl, in contrast to the present study in which 1.7 mg/dl was used as a cut-off to define hypomagnesemia. And indeed, if we re-analyze our data with a cut-off serum magnesium value of 1.8mg/dl, 15,1% of the entire population is diagnosed with hypomagnesemia: 11.5% of the overweight and obese patients and 32.6% of the patients with DM2, which is more in line with the Guerrero-Romero study and to studies performed in patients with DM2 (14% to 48%) [18][19][20]. Also, racial differences in serum magnesium levels have been reported.…”
Section: Discussionsupporting
confidence: 76%
“…This inflammation might contribute to the onset of IR [14,17]. The prevalence of hypomagnesemia in T2DM has been reported to range between 14 and 48%, meaning that millions of people worldwide are affected [18][19][20]. In DM patients, magnesium deficiency is associated with the development of micro-and macrovascular complications [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, hypomagnesaemia is usually indicative of a systemic Mg deficit. Depletion in intracellular and serum ionized Mg can be found in many subjects with total serum Mg still in the normal range [12]. We have recently confirmed that diabetic older patients are more prone to hypomagnesaemia; this condition being closely related with metabolic control as measured by glycated hemoglobin even after adjustment for relevant confounders.…”
supporting
confidence: 51%
“…Mg deficiency in type 2 diabetes may take the form of a chronic latent Mg deficit rather than an overt clinical hypomagnesaemia [12], and may have clinical importance because the Mg ion is a crucial cofactor for many enzymatic reactions involved in a myriad of metabolic processes. The Mg ion plays a key role in the regulation of the effects of insulin and insulin-mediated cellular glucose intake.…”
Section: Mg Deficiency and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation